Pelatihan Penentuan Rute Pendistribusian Outlet Pada CV. Healfit Pangan Sehat (Dietgo Kitchen) - Yulianto, Irwan; Martikasari, Arida Murti; Zulkifli, Ridwan (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
High distribution costs pose a significant challenge for Small and Medium Enterprises (SMEs), such as Dietgo Kitchen in Bandung, which inefficiently relies on third-party online delivery services to distribute ingredients to its seven branches. This point-to-point logistics issue increases total operational costs and erodes profit margins. To address this, an intervention in the form of Vehicle Routing Problem (VRP) Implementation Training and Mentoring was conducted for the company's distribution team, aimed at utilizing the company's unoptimized food trucks for autonomous delivery. The training focused on mastering the VRP heuristic methods, namely Nearest Neighbor and Nearest Insertion, to determine optimal delivery routes from the central warehouse to all outlets. This mentoring included actual field data acquisition, route simulations, and structured delivery management training. Evaluation results showed a significant positive impact, with a 43.71% reduction in delivery costs compared to the average of the previous three months. While employee adaptation to the new VRP system and methods is still required, this implementation demonstrates that VRP is an effective strategic instrument for achieving delivery route efficiency and reducing routine operational costs for SMEs.